The problems of low cost housing ownership in Selangor / Norhasrina Mohd Nasir - Mohd Nasir, Norhasrina (2010)
Shelter is a basic a human need as food and water. Today, many people in Third World countries live in sub-standard housing or lack shelter altogether. Technological improvement and economic development has affected human life. During this period, people eagerly to find enjoyment in this world. Therefore, preparation home becomes very important, especially to low income groups urban areas to meet the needs of their major. With research to Selangor area, this research would see the problems of low cost housing in Selangor because Selangor is the most developed state in Malaysia. Many variety of development can be seen in Selangor. However there the things that until now are still happened in Selangor that is about issue of low cost housing in Selangor. Nowadays, an issue about low cost house is increasingly dealt with elsewhere. Whether because of inefficient management resulted, many squatters still have in Selangor. Squatters and housing are among the main subject of government focus in each development programmme in Malaysia. Although government has been announced for zero squatters policies, but it still have many in Selangor. So with government policies in Selangor, many steps taken to encourage developer to built low cost house in Selangor when it is different policy between states in Malaysia. Basically depends on area of the state. In this research, the author would state the problems of low cost housing with policies in Selangor. Survey method was based on interviews with those in related department. The information from the interviewers will be made in primary data for this study. In addition, theoretical studies also explain in the policies, the implementation of housing programs in the country in general. The main focus is given to the scenario of low cost housing development in Selangor.